2018
DOI: 10.3390/su10041204
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Venture Capital Investments: An Enabler Investigation

Abstract: Investing in sustainable projects can help tackle the current sustainability challenges. Venture capital investments can contribute significantly to the growth of sustainable start-ups. Sustainable venture capital (SVC) research is just emerging. This paper identifies enablers for sustainable venture capital investments in Saudi Arabia taking into account different stakeholders and firm's tangible and intangible resources. Using perspectives from venture capital experts in Saudi Arabia and the grey-based Decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 104 publications
(124 reference statements)
0
16
0
2
Order By: Relevance
“…It will be interesting to investigate the impact of experience on acquisitions in other high-tech industries such as biotechnology industries. The results could be similar or different depending upon the industry and technology characteristics which affect motivation and mediating factors of private target acquisition [39,40]. Note: Heteroscedasticity-consistent t-ratios are in parentheses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It will be interesting to investigate the impact of experience on acquisitions in other high-tech industries such as biotechnology industries. The results could be similar or different depending upon the industry and technology characteristics which affect motivation and mediating factors of private target acquisition [39,40]. Note: Heteroscedasticity-consistent t-ratios are in parentheses.…”
Section: Discussionmentioning
confidence: 99%
“…These results imply that early VC-backed experience effectively mitigates information asymmetry related to private target acquisition by NASDAQ firms in high-tech industries. Early VC-backed firms have developed firm-specific abilities to evaluate private companies with intangible resources, to assess and use information in the process of M&A deals, and to hedge risks and uncertainty [38,39].…”
Section: Empirical Specificationsmentioning
confidence: 99%
“…As mentioned above, intangible assets from VC firms, such as their experience and knowledge, become valuable resources that contribute to the success and sustainability of startups [12,[49][50][51]. In order to generate high performance and sustain business activity, a firm needs the ability to absorb and utilize the acquired intangible assets.…”
Section: Moderating Effects Of Startups' Learning Capability: Absorptmentioning
confidence: 99%
“…Extant research on VC companies has examined a wide variety of topics, such as the characteristics of invested startups, the influence of VC investment on firms [7][8][9][10][11][12][13], the investment process of VC companies [5,6,14,15], the relationship between VC companies and startups [2], and the investment of VC companies by stage. Despite extensive academic efforts, the impact of VC financing on firm performance is still unclear, as previous studies have shown mixed results on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Investing in sustainable projects can help one to deal with current sustainability challenges. VC investments can contribute significantly to the growth of sustainable start-ups [26]. In the traditional investment environment, entrepreneurs' preparedness has a significant impact on investors' investments.…”
Section: Influence Of Entrepreneurs' Backgrounds On Financing Effectmentioning
confidence: 99%